Role of NGOs, CBOs and Private Organizations for Efficient Management of Municipal Solid Waste in Kathmandu Valley - Bhattarai, Ram Chandra (Tribhuvan University Journal, 2010)
This paper attempts to discuss the role of Community based, nongovernmental and private institutions for the management of municipal solid waste in Kathmandu Valley. It is based on secondary information available from different sources. Studies reveal that private institutions, Community Based Organizations (CBOs) and Non Governmental Organizations are collecting about 60% of the total waste generated within Kathmandu Valley from door-to-door of the generators. These institutions are also contributing to reduce about 40% of the municipal cost for the collection of waste. Study reveals that household segregation and compositing is considered as the best option for the efficient management of municipal solid waste in the cities of developing countries like Kathmandu. This is possible only through the involvement of CBOs, NGOs and private sector.